1996
DOI: 10.1520/jfs14033j
|View full text |Cite
|
Sign up to set email alerts
|

The Sexually Sadistic Serial Killer

Abstract: This article explores characteristics and crime scene behavior of 20 sexually sadistic serial murderers. The pairing of character pathology with paraphilic arousal to the control and degradation of others is examined as it manifests itself in their murders. Commonalities across murders and across murderers are highlighted, i.e., the execution of murders that are well-planned, the use of preselected locations, captivity, a variety of painful sexual acts, sexual bondage, intentional torture, and death by means o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
90
0
1

Year Published

2003
2003
2011
2011

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 156 publications
(96 citation statements)
references
References 4 publications
5
90
0
1
Order By: Relevance
“…Only three studies [6,7,15] used stan-dardized diagnostic criteria, and they found even higher rates of sexual sadism or sadomasochism (75% according to DSM-III-R [6] ; 70% according to the Clarke Sex History Questionnaire for Males [15] ). Differences between studies probably depend also on sample selection, with higher prevalence rates in those studies focusing on serial sexual murderers [5,11,21,25,27] and lower rates in samples with mainly one-time offenders [1,2,20] .…”
Section: Discussionmentioning
confidence: 99%
“…Only three studies [6,7,15] used stan-dardized diagnostic criteria, and they found even higher rates of sexual sadism or sadomasochism (75% according to DSM-III-R [6] ; 70% according to the Clarke Sex History Questionnaire for Males [15] ). Differences between studies probably depend also on sample selection, with higher prevalence rates in those studies focusing on serial sexual murderers [5,11,21,25,27] and lower rates in samples with mainly one-time offenders [1,2,20] .…”
Section: Discussionmentioning
confidence: 99%
“…For instance, Warren, Hazelwood, & Dietz, 1996), using information from case files, report that 16 out of 20 sadistic sexual murderers showed evidence of violent sexual fantasies that had been assimilated into their ritualized, repetitious offences.…”
Section: Sexual Fantasy and Behaviormentioning
confidence: 99%
“…Sadistic sexual aggressors of women (rapists or sexual murderers) have been described in several studies (Beauregard & Proulx, 2002;Brittain, 1970;Gratzer & Bradford, 1995;Groth & Birnbaum, 1979;Knight & Prentky, 1990;Marshall & Kennedy, 2003;Marshall, Kennedy, Yates, & Serran, 2002;Proulx, Blais, & Beauregard, 2006;Proulx et al, 1999;Warren, Hazelwood, & Dietz, 1996). The sadistic sexual aggressor carefully plans his offence.…”
Section: The a → C Equationsmentioning
confidence: 99%